Global transcriptome analysis of the aphelid Paraphelidium tribonemae supports the phagotrophic origin of fungi. (December 2018) - Torruella, Guifré; Grau-Bové, Xavier; Moreira, David; Karpov, Sergey; Burns, John; Sebé-Pedrós, Arnau; Völcker, Eckhard; López-García, Purificación
Abstract Aphelids are little-known phagotrophic parasites of algae whose life cycle and morphology resemble those of the parasitic rozellids (Cryptomycota, Rozellomycota). In previous phylogenetic analyses of RNA polymerase and rRNA genes, aphelids, rozellids and Microsporidia (parasites of animals) formed a clade, named Opisthosporidia, which appeared as the sister group to Fungi. However, the statistical support for the Opisthosporidia was always moderate. Here, we generated full life-cycle transcriptome data for the aphelid speciesParaphelidium tribonemae . In-depth multi-gene phylogenomic analyses using several protein datasets place this aphelid as the closest relative of fungi to the exclusion of rozellids and Microsporidia. In contrast with the comparatively reducedRozella allomycis genome, we infer a rich, free-living-like aphelid proteome, with a metabolism similar to fungi, including cellulases likely involved in algal cell-wall penetration and enzymes involved in chitin biosynthesis. Our results suggest that fungi evolved from complex aphelid-like ancestors that lost phagotrophy and became osmotrophic. Guifré Torruella et al. present the first transcriptome data of an aphelid species, which multi-gene phylogenomic analyses place as the closest relative of fungi. They are able to infer a free-living-like aphelid proteome and suggest that fungi evolved through the loss of phagotrophy from aphelid-like ancestors.